Ceramic Membranes Applied in Separation Processes - da Silva Biron, Dionisio (Topics in Mining, Metallurgy and Materials Engineering,, 2018)
This book covers diverse types of ceramic membranes applied in separation processes. The authors present the preparation methods and well as the main application of ceramic membranes. Modules, microfiltration and ultrafiltration are topics described within the text. The final chapter focuses on water and wastewater treatment by membranes separation processes.